Review of Bolder and Fender Needs at Batang Serai Pier in Deli Serdang Regency, North Sumatra Province - Ilham, Chairul Insani; Santoso, Santoso; Panggabean, Yunita; Mardinata, Muhammad Rico Putra (IWTJ : International Water Transport Journal, 2023)
Batang Serai Pier is a pier located in the Belawan Service Unit, the Belawan Service Unit also has 2 passenger transportation routes, namely Sundari Pier and Batang Serai Pier, the existing pier is also one of the connections between islands and is important for the surrounding community to buy basic necessities so that it has the potential to advance the economy in the surrounding area. Batang Serai Pier also needs to be updated with facilities that are no longer suitable for use, so that the pier can be operated more efficiently, so the author reviewed Batang Serai Pier which generally does not receive enough attention for maintenance and the suitability of the pier through the author's analysis using a calculation method, the results obtained were the need for ship berthing facilities such as there should be changes to the number ofboldas many as 6 units with a distance betweenbold by 4 meters and changes in the Number fenderas many as 5 units with a distance betweenfenderas large as 5 meters. The results obtained from calculations based on the Transportation Planning Book written by Bambang Triatmodjo in 2009 must be adjusted and facilities that are no longer suitable for use must be updated in their placement.Bold FenderIt is necessary to carry out renovations so that there is no more damage to the pier due to ships mooring at the pier which causes the pier to erode if the mooring process is not carried out correctly.